Monique Bosco: Les Lamentations de la vieille en ce jour du Kippour - Minelle, Cristina (Romanica Silesiana)
The article examines the ways in which Monique Bosco, in her « Les lamentations de la vieille en ce jour du Kippour », combines the main features of the lamentation - an ancient genre which was employed in the Bible - with elements typical for the short story. The clear presence of biblical roots makes the modern setting and theme of the text unusual and, not infrequently, unsettling for the reader. Key words: Short Story; Lamentations; Bible; Psalms